Optimization of ISSI Stock Portfolio using Single Index Models in 2013-2017 - Dzanurrahmana Zein, F; Aimmatul Umah, K; Asyaria, K; Herianingrum, S; Syifaul Qulub, A; Alif Rusmita, S (KnE Social Sciences, 2019)
The article's abstract is not available.